BAKAT DAN PERANNYA DALAM BELAJAR DI SDN 12 PINANG AWAN - Dewi Fitriana; Vilmaisari; Yelly Martaliza; Syovia Lolita; Rezki Putra; Husni Nofrita; Fitri Sari Angkat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to explore students’ talents and examine their roles in the learning process, as well as to analyze teachers’ roles in developing students’ talents at the elementary school level. The study employed a qualitative approach with a descriptive-interpretative design and was conducted at SDN 12 Pinang Awan Solok Selatan Regency. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed thematically using an interactive analysis model. The findings reveal that students possess diverse talents, including academic, artistic, athletic, and social talents, which function as psychological capital that enhances motivation, learning engagement, self-confidence, and meaningful learning experiences. The study also shows that teachers play a vital mediating role in recognizing and facilitating students’ talents, although such practices have not yet been systematically integrated into differentiated instructional strategies. These findings suggest that talent-sensitive learning practices are essential for fostering holistic student development and for strengthening psychologically supportive learning environments in elementary education.